Virtual hype meets reality: Users' perception of immersive journalism. (October 2021) - Nielsen, Søren Lund; Sheets, Penelope
This study responds to recent calls to investigate how media users perceive virtual reality technology in journalism. Within a uses and gratifications framework, focus group participants were asked to experience recent immersive journalistic productions and discuss their reactions. Six distinct gratifications were identified, which cluster into gratifications related to experience, affect, and action . Despite clear reservations about the technology, users see great potential for journalistic use. If employed responsibly, users think virtual reality can add considerable value to mainstream journalistic productions, potentially boosting engagement and trust. Researchers and practitioners can benefit from this initial study of users' impressions of and reactions to immersive journalism.